The Impact Of Pandemic On Tax-Paying Compliance - Endang Kristiawati; Wilda Sari; Ali Afif; Jaurino Jaurino; Risal Risal; Febriati Febriati (Journal of Accounting and Taxation, 2023)
This study aims to determine taxpayers' perception and financial conditions during the pandemic on the level of tax compliance in Micro, Small, and Medium Enterprises (MSMEs). The research method used in this study is a data quality test consisting of validity and reliability testing, classical assumption test consisting of normality test, multicollinearity test and heteroscedasticity test, and hypothesis testing consisting of multiple regression analysis. The variables in this study are taxpayers' perceptions and financial conditions during the pandemic. The results of this study indicate that the perception of taxpayers and financial conditions during the pandemic has a positive effect on compliance with paying taxes on MSMEs in Pontianak City. Theory of Planned Behavior supports this research to explain taxpayers' perception that all actions or behavior begin with intention. Behavioral intentions are formed by attitudes toward behavior, social norms and control over perceived behavior. Government policies in tax incentives provide convenience for MSME actors because MSME taxpayers do not need to deposit taxes owed but only need to make a realization report every month. This will increase taxpayer awareness in fulfilling their tax obligations.